ANALISIS TINGKAT KETIDAKPUASAN NASABAH TERHADAP PENANGANAN KLAIM ASURANSI KENDARAAN BERMOTOR PADA PT. JASARAHARJA PUTERA CABANG PEKANBARU - Vicky Masril Rahmat Saputra; Jushermi -; Henny Noviasari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study held in PT. Jasaraharja Putera Pekanbaru branch in order to analyze JP-Insurance customers’ dissatisfaction on vehicles insurance claim. The benefit of this study are expected to become an valueable input for PT. Jasaraharja Putera in order to comprehend all aspects which are still can’t satisfy customers, particularly in claim handling service. This study use primary and secondary data. Data collected by using questioner and interview method. Population are JP-Insurance customers. Sample is formulated by using Slovin and consists of 84 respondents which are then selected by using purposive sampling technique. Data descriptively analyzed by using Importance Performance Analysis (IPA).This study reveals that averagely respondents less satisfied with the claim handling done by PT. Jasaraharja Putera Pekanbaru branch. The most dissatisfaction are rated from loss survey (53%); claim documents (53,6%); premium check (55,9%) and loss report (60,7%). It is recommended to improve some claim handling aspects such as: flexible time of premium payment; claim payment during the lateness of premium payment; simplifying the accident information investigation; flexibility of replacement amount; simplifying to get claim forms and flexibility of claim documents preparation.Keywords: Insurance, Claim Handling, Service Quality, and Satisfaction